The Phenomenon of De Gustibus Non Est Disputandum and Experience-Based Marketing Instruments: A Case Study of Visitors to Bivak Terrace Coffee Shop - Alvina Rahma Anggraeni; Risha Fatikha Sari; C.J. Lagerkvist; Muhammad Imam Taufiq; Sina Nematizadeh (Tinta Emas Publisher, 2025)
This study explores the impact of experiential marketing and perceived quality on the purchase decisions of processed coffee products at Bivak Terrace coffee shop in South Tangerang. Using a purposive sampling method, data were collected from 43 respondents and analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS). The results indicate that experiential marketing significantly influences purchase decisions, whereas perceived quality, despite having a positive impact, does not significantly affect consumer purchase decisions. The findings suggest that experiential elements such as packaging and consumer experience play a more crucial role than product quality alone in influencing purchase decisions. The study recommends enhancing product quality to better satisfy consumers and maintain competitive advantage.